Finite Element Analysis on Badminton Racket Design Parameters - Nasruddin, Fakhrizal Azmy.; Harun, Muhamad Noor.; Syahrom, Ardiyansyah; Abdul Kadir, Mohammed Rafiq; Omar, Abdul Hafidz; Öchsner, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This work identifies the characteristics of racket design parameters that influence racket performance.  It presents the finite element analysis of several designs of badminton rackets and compares them to experimental results for validation. Designing a racket requires a comprehensive understanding of racket performance characteristics. Essentially, racket performance is related to the sweet spot, which is the spot on the racket head that produces the most power and control when it strikes a shuttlecock. Determining a coefficient of restitution can help to identify the sweet spot on a racket. By analyzing several head shape designs, it becomes apparent that isometric head shape rackets produce better coefficients of restitution compared to oval and round ones. It is recommended that the racket design consist of low string tension, stiffer racket shafts and bigger head size in order to produce higher shuttlecock speed.
Introduction -- Coefficient of Restitution (COR) in Badminton Racket -- Effect of String Tension toward Racket Performance -- Stiffness of Badminton Racket -- Head Shape Design Analysis of Conceptual Badminton Racket -- Conclusion.
Keywords: Mechanics, Applied; Solids; Sports sciences; Engineering design; Solid Mechanics; Sport Science; Engineering Design